Knowledge, attitude and practices of nurses towards medical exmination at Ndola central and Arthur Davidson children hospitals in Ndola district - Chileshe, Jaclyn Mulenga Kasongo (Lusaka; University of Zambia, School of Medicine, 2009)
The study was aimed at determining the knowledge attitude and practices of nurses towards medical examination. The medical examination service has been undeutilised by nurses and literature review shows that there has been an increase in morbidity and mortality rates among health workers in general.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references .
Keywords: Medical examinations; Medical examinations -- nurses -- Ndola district -- attitudes